Floral resource strips enhance parasitoid abundance and diversity in apple orchards and promote agroecological advances in a South African biosphere reserve - Ratto, Fabrizia; Steward, Peter Richard; Sait, Steven; Haran, Julian; Gaigher, Rene; Pryke, James; Samways, Michael; Kunin, William (2025)
Agricultural intensification drives insect declines, including those of parasitoids, through landscape simplification and extensive use of synthetic pesticides. Spatially heterogeneous agricultural landscapes are potentially important biodiversity reservoirs where non-crop habitats may support populations providing ecosystem services to farming. However, there is a need to find methods to support this transition to more sustainable farming and support the progressive concept of biosphere reserves. We focus here on the relationship between apple orchards and sclerophyllous natural fynbos vegetation in the megadiverse Kogelberg Biosphere Reserve, Cape Floristic Region, South Africa. We established patches of floral resources within apple orchards, which are embedded in landscapes, equivalent to the transition zone of the KBR, with varying proportions of natural habitat in a 500 m radius around orchards. We assessed the role of these enhanced floral resources for supporting parasitoid abundance, species richness, and diversity inside orchards, and compared these metrics to those in ruderal vegetation around orchards and in nearby natural vegetation. Further, we assessed the effect of semi-natural vegetation in the surrounding landscape mosaic on parasitoids in orchards. Floral enhancement improved parasitoid abundance and influenced assemblage composition within apple orchards. However, non-crop ruderal habitat immediately adjacent to orchards supported greater abundance and richness of parasitoid species, while natural fynbos supported even richer parasitoid assemblages. Vegetation within orchards and landscape complexity enhanced parasitoid assemblages inside and surrounding the orchards. Our study shows that increasing floral resources within orchards improves local diversity of parasitoids within agroecosystems in the Biosphere Reserve. In doing so, this improves levels of biodiversity and increases parasitoid richness within the biosphere transition zone, supporting a shift from conventional production to a more biodiversity-friendly agroecological approach.